2008
DOI: 10.1371/journal.pone.0003429
|View full text |Cite|
|
Sign up to set email alerts
|

HLA-Driven Convergence of HIV-1 Viral Subtypes B and F Toward the Adaptation to Immune Responses in Human Populations

Abstract: BackgroundCytotoxic T-Lymphocyte (CTL) response drives the evolution of HIV-1 at a host-level by selecting HLA-restricted escape mutations. Dissecting the dynamics of these escape mutations at a population-level would help to understand how HLA-mediated selection drives the evolution of HIV-1.Methodology/Principal FindingsWe undertook a study of the dynamics of HIV-1 CTL-escape mutations by analyzing through statistical approaches and phylogenetic methods the viral gene gag sequenced in plasma samples collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Analysis of a European cohort supported the accumulation of HIV-1 adaptations to CTL responses over the period 1985 to 2005 (28), as did a South American study of HIV-1 subtypes B and F over the same time period (29). More strikingly, a recent study of 9 global cohorts revealed a strong positive correlation between the prevalence of HLA-B*51 and that of its associated HIV-1 reverse transcriptase (RT) I135X polymorphism in circulating sequences (22).…”
Section: H Uman Leukocyte Antigen (Hla) Class I-restricted Cd8mentioning
confidence: 71%
“…Analysis of a European cohort supported the accumulation of HIV-1 adaptations to CTL responses over the period 1985 to 2005 (28), as did a South American study of HIV-1 subtypes B and F over the same time period (29). More strikingly, a recent study of 9 global cohorts revealed a strong positive correlation between the prevalence of HLA-B*51 and that of its associated HIV-1 reverse transcriptase (RT) I135X polymorphism in circulating sequences (22).…”
Section: H Uman Leukocyte Antigen (Hla) Class I-restricted Cd8mentioning
confidence: 71%
“…The PCR conditions were: denaturation for 2 min at 94 8C, primer annealing/elongation: 10 cycles of 15 s at 94 8C, 30 s at 55 8C, 1.5 min at 72 8C followed by 25 cycles of 15 s at 94 8C, 30 s at 55 8C, 1.5 min at 72 8C with addition of 5 s to the elongation time per cycle; final elongation of 7 min at 72 8C. The first round primers are based on the methodology published by Dilernia et al [12]. This methodology and primer sequences were kindly provided by Prof. Richard Harrigan (HIV Centre of Excellence, Vancouver, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…22 The set of sequence includes the viral gene gag, the viral gene env, and full-length viral genomes as schematized in Fig. 1 23 ).…”
Section: Sequences Analyzedmentioning
confidence: 99%